REKONSTRUKSI DEEP LEARNING BERBASIS ETNO-PEDAGOGI DALAM PENDIDIKAN SAINS SEKOLAH DASAR - Rahmawati, Qoriah; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing complexity of environmental and socio-ecological challenges requires science education to move beyond memorization-oriented instruction toward more meaningful and culturally situated learning experiences. However, science learning practices often remain disconnected from students’ cultural realities and indigenous ecological knowledge. This review article aims to analyze the reconstruction of ethno-pedagogy and deep learning in elementary science education to strengthen reflective ecological thinking and contextual scientific literacy. This study employed a narrative systematic review by examining articles indexed in Scopus, ERIC, Google Scholar, and ScienceDirect published between 2015 and 2026. The review identified four major themes, namely the transformation of science education toward situated learning, the role of ethno-pedagogy in culturally responsive education, deep learning as reflective and transformative learning, and the reconstruction of indigenous ecological knowledge into contextual scientific literacy. The findings indicate that ethno-pedagogical deep learning provides opportunities to reconstruct science learning through culturally grounded inquiry, environmental exploration, and reflective interpretation of environmental realities. In conclusion, the integration of ethno-pedagogy and deep learning offers a conceptual perspective for developing meaningful elementary science learning by connecting local ecological knowledge, reflective inquiry, and contextual scientific literacy.